Satisfaction with the free wireless connection among Muslim university students - Imran , Ayub Ilfandy; Wok, Saodah (2011)
Technological change in an organization gives impacts towards its members. In Islamic educational institutions, for example, International Islamic University Malaysia (IIUM), the introduction of a new technology affects students in many aspects. This study was conducted to investigate the impacts of a new technological implementation, the Free Wireless Connection (FWC), among Islamic Revealed Knowledge and Human Sciences (IRKHS) students. IRKHS, as the most populated faculty in IIUM, is divided into two main academic divisions, namely, Islamic Revealed Knowledge (IRK) and Human Sciences (HS). The main objective of this study is to see the patterns of technological adoption among Muslim students. The specific objectives are: (1) to find out the level of Internet and FWC usage among IIUM undergraduate students; (2) to find out the differences in adoption patterns of FWC in terms of gender, nationality, and academic division; (3) and to find out students’ level of satisfaction towards the new technology. This study applied a survey research design. Descriptive and inferential statistics will be employed to answer the research objectives.